GAMBARAN TINGKAT KECEMASAN PASIEN GAGAL GINJAL MENJALANI TERAPI HEMODIALISA DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG TAHUN 2017 - Rika yoni (Menara Ilmu, 2018)
Hemodialysis is a high technology as a substitute for kidney function to remove certainresidual metabolism or toxins from human blood circulation through semi permiabelmembrane as blood and dialysis fluid in artificial kidney where diffusion, osmosis and ultrafiltration process occurs. From WHO data recorded the world's kidney failure patients morethan 500 million people, is the disease ranked 12th highest cause of death. Based on datafrom the Association of Nephrology of Indonesia in 2011 there are about 12,500 patients withrenal failure undergoing routine hemodialysis therapy. Riskesdas 2013 shows the prevalenceof renal failure in West Sumatra by 0.2%. The year 2014 in West Sumatra recorded 368patients with kidney failure and 191 of them undergoing hemodialysis. The purpose of thisstudy to determine the picture of anxiety levels of patients with renal failure undergoinghemodialysis therapy at Siti Rahmah Padang Islamic Hospital. The type of research used isdescriptive. The study was conducted in March to April 2017, the study population was 30people. The sample in this study were 30 respondents, sampling technique using totalsampling. The data were collected using a HARS questionnaire to find out anxiety levels ofpatients undergoing hemodialysis therapy.The result of this research was 1 patient (3.3%) had mild anxiety level, moderate anxietylevel 5 patients (16.7%), severe anxiety level as many as 18 patients (60.0%), and severeanxiety level as many as 6 patients (20.0%) The conclusion of this study is that patients whoundergo hemodialysis therapy in RSI Siti Rahmah Padang many who experience the level ofsevere anxiety. So the researchers suggest to hospital officials in order to reduce anxietypatients by providing counseling and counseling.Keywords: Patient Anxiety Level With Kidney Failure, Hemodialysis Therapy.